The Impact of Agile Suppy Chain Strategy on Sustainability Performance with Company’s Sustainability Reporting: Evidence from Pulp & Paper Industry in Indonesia - Erwin Erwin (Jurnal Ilmiah Akuntansi, 2021)
This study examines the agile supply chain strategy (SCS) in pulp & paper firms in Indonesia, impacting the sustainability performance via mediator variables. Applying the theory of resource-based view (RBV) and theory of dynamic capabilities view (DCV) to explore these links, several hypotheses are constructed regarding information sharing with customers (ISC), collaboration with suppliers (CS), and advanced manufacturing technology (AMT) as a mediator variable. The research is examined by partial least square-structural equation model (PLS-SEM), and 102 manufactures in Indonesia gather the data sample. The empirical findings show that ISC, CS and AMT mediate agile SCS on sustainability performance. Theoretically, the study reveals that complements between RBV and DCV create synergy relation agile SCS on sustainability performance through some mediator variables. In practical view, these findings help executives satisfy their stakeholders for executing agile SCS in pulp & paper industries.